Pengaruh Pendekatan Steam-Loose Parts terhadap Kemampuan Literasi Numerasi Anak Usia Dini - Asyifa’un Nufus; Fajar Arianto; Utari Dewi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The study aimed to identify the approach STEAM-Loose Parts of the ability of literasi numeracy in children aged 3-4 years in Pre School of SKB Sidoarjo. During the observation, several pre school of SKB Sidoarjo were found to have low numeracy skills among the children. The low numeracy skills in children aged 3-4 years are caused by the general nature of mathematics education, which is rarely linked to activities or daily life. However, numeracy skills can help children solve everyday life problems. This study uses the one group design pretest-postest method and uses non parametric data analysis techniques with the help of the wilcoxon match pairs test formula because the subjects only 6 childrens. The result of this research shows that getting the pre-test average is 43,3 and the post-test of 85,0 data shows that the STEAM-Loose Parts learning has a significant impact on the numeration capabilities of 3-4 years old in the pre school of SKB Sidoarjo.